The Relationship of Acupuncture Use to the Endometriosis Risk in Females With Rheumatoid Arthritis: Real-World Evidence From Population-Based Health Claims - Chen, Wei-Jen; Livneh, Hanoch; Hsu, Chien-Hui; Hu, Ying-To; Lai, Ning-Sheng; Guo, How-Ran; Tsai, Tzung-Yi (Frontiers in Medicine, 2021)
Objectives: Women affected by rheumatoid arthritis (RA) have a higher risk of endometriosis, an estrogen-dependent, chronic inflammatory disease. Though acupuncture has long been a safe and effective therapy for treating inflammatory conditions, it is unclear whether it could prevent the onset of endometriosis. This study aims to determine the effect of acupuncture on the subsequent risk of endometriosis in female RA patients. Methods: Between 1998 and 2010, female subjects with RA, were recruited from a nationwide database (5736 patients; age ≥20 years). Enrolled patients included 2407 acupuncture users and 2407 non-users randomly selected using propensity scores. The occurrence of endometriosis was recorded through the end of 2012. Cox proportional hazards regression was used to estimate the adjusted hazard ratio (HR) for acupuncture use. Results: During the follow-up period, 35 acupuncture users and 94 non- users developed endometriosis, with incidence rates of 2.36 and 4.91 per 1000 person-years, respectively. Acupuncture use was associated with a 55% lower endometriosis risk (adjusted HR, 0.45; 95% confidence interval, 0.31–0.65). Those who received high intensity acupuncture (≥15 packages) had the greatest benefit. Conclusions: Findings suggest that adding acupuncture to conventional therapy may decrease the subsequent endometriosis risk in female RA patients. Prospective randomized trials are recommended to further clarify whether the association revealed in this study supports a causal link.